Advances in the Potential Biomarkers of Epilepsy - Kobylarek, Dominik; Iwanowski, Piotr; Lewandowska, Zuzanna; Limphaibool, Nattakarn; Szafranek, Sara; Labrzycka, Anita; Kozubski, Wojciech (Frontiers in Neurology, 2019)
Epilepsy is a group of chronic neurological disorders characterized by recurrent, spontaneous and unpredictable seizures. It is one of the most common neurological disorders, affecting tens of millions of people worldwide. Comprehensive studies on epilepsy in recent decades have revealed the complexity of epileptogenesis, in which immunological processes, epigenetic modifications and structural changes in neuronal tissues have been identified as playing a crucial role. This review discusses the recent advances in the biomarkers of epilepsy. We evaluate the possible molecular background underlying the clinical changes observed in recent studies, focusing on therapeutic investigations and the evidence of their safety and efficacy in the human population. This article reviews the pathophysiology of epilepsy, including recent reports on the effects of oxidative stress and hypoxia, and focuses on specific biomarkers and their clinical implications, along with further perspectives in epilepsy research.